ANTECEDENTS AND CONSEQUENCES OF WETLAND-BASED FORENSIC ACCOUNTING IN SOUTH KALIMANTAN: A QUALITATIVE STUDY - Susi Apriana; Syahrial Shaddiq; Achmad Suhaili; Muhammad Ihsanul Arief; Erlan Titoe; Steven Kenli (Al-Mubin, 2026)
Forensic accounting has become a global concern in addressing increasingly complex economic and environmental challenges, particularly in detecting and preventing opaque financial practices, fraud, and resource misuse. The concept of forensic accounting focuses on evidence-based financial investigations to uncover irregularities in asset management, including in sectors related to the wetland environment and sustainable economics. Amid growing concerns about climate change, environmental degradation, and natural resource exploitation, forensic accounting plays a crucial role in ensuring accountability and transparency in financial management, thereby more effectively supporting sustainable development policies. This study aims to evaluate the antecedents and consequences of forensic accounting implementation on economic, environmental, and social aspects, particularly in improving accountability, transparency, and mitigating financial risks. This study uses a qualitative approach using ethnographic methods, in-depth interviews, participant observation, and document analysis. The results show that antecedent factors include weak understanding of regulations, limited human resources, and limited data, while the consequences of forensic accounting implementation have a positive impact on the efficient use of public funds, strengthening governance, and improving social welfare. These findings are expected to provide a foundation for policymakers in designing strategies for implementing forensic accounting that are more effective, inclusive, and sustainable in South Kalimantan